A Comparative Analysis of Traditional and Online Assessments: Perceptions and Performance of Undergraduate Students - Rubab, Iram; Imran, Areeb (Pakistan Journal of Humanities and Social Sciences, 2023)
This study aims to conduct a comparative analysis of traditional and online assessments and examine the perceptions and performance of undergraduate students towards these assessment methods. The study holds significance because it provides valuable insights into the effectiveness and appropriateness of these assessments, considering the recent surge in online education and assessments of undergraduates. An online survey questionnaire divided into three sections was used as a research tool used for data collection, addressing the advantages/disadvantages, perceptions, and performance of students. The sample population consisted of 120 students from three universities: GC Women University Sialkot, Punjab University, and Government Murray College. The findings reveal the traditional assessment methods are better than online which make positive impact on the performance of undergraduate students. This study contributes to the existing literature and provides recommendations to improve assessment practices in universities to ensure valid measurement of knowledge and abilities. Overall, the research provides significant knowledge into students' experiences and directs institutions towards improving evaluation procedures to meet the needs of learners.